In Situ Electrochemical Regeneration of Degraded LiFePO4 Electrode with Functionalized Prelithiation Separator - Fan, Min; Meng, Qinghai; Chang, Xin; Gu, Chao‐Fan; Meng, Xin‐Hai; Yin, Ya‐Xia; Li, Hongliang; Wan, Li‐Jun; Guo, Yu‐Guo (Advanced energy materials, 2022)
Lithium‐ion batteries (LIBs) are in great demand for their impressive successes in serving people's daily life. Concomitantly, recycling the retired LIBs has also aroused the enthusiasm of widespread studies due to its great significance in the sustainable development of LIBs. Among the spent LIBs, LiFePO4 (LFP) is the main force because of its widespread use in electric vehicles and grids due to its stability and favorable price. However, considering the low cost of LFP manufacture as well as the abundance of Fe and P, traditional metallurgy processes are not economically feasible for recycling LFP because of high energy consumption and tedious steps. Here, this work proposes a green recycling method to directly regenerate the degraded LFP electrode via an in situ electrochemical process with a functionalized prelithiation separator. Compared with the existing recycling strategies for LFP batteries, the proposed method takes full advantage of the degraded cathode scraps without destroying the original structure, greatly reducing the cost of the remanufacture of the cathode electrodes simply via a prelithiation technique. Degraded LiFePO4 (D‐LFP) electrodes are directly reassembled into a new battery with a functionalized prelithiation separator and fresh graphite anode. Extra Li+ ions provided by the sacrificial lithium‐containing layer compensate the Li+ loss in the D‐LFP during the initial electrochemical process and thus the capacity of the regenerated battery is largely restored.